The Incidence of Palatal Fistula Postpalatoplasty in Children with Dental Caries: A Multi Centre Study - Utama, Defry; Buchari, Frank; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Cleft lip and/or palate (CL&/P) is the most common congenital craniofacial abnormality, affecting approximately 1 in every 700 newborns. Patients with cleft lip and/or palate (CL&/P) generally display poor oral hygiene and a higher prevalence of caries. This may be due to the difficulty in achieving adequate plaque control associated with dental anomalies and defects from the lips and/or palate. Palatal fistula is a significant complication following cleft palate repair. It is the aim of this research to find correlation between palatal fistula and dental caries. Patient and Method: Patients with unilateral complete cleft palates admitted to the Cipto Mangunkusumo hospital, Adam Malik hospital within the period July 2012 till March 2013 were included in this study. All cases underwent modified two flap palatoplasty leaving lateral periosteum technique and follow-up were done in two weeks to see if there are any palatal fistula. Result: Thirty eight patients with unilateral cleft palate were enrolled in the study. Fifteen (39.5%) of them are boys and 23 (60.5%) are girls. Fifteen of the patients (41.7%) had dental caries, with six patients (40%) had palatal fistula in the follow up after palatoplasty, while there was none (0%) of the 21 (58.3%) patients that were found negative for dental caries developed a fistula. Conclusion: Dental caries is one of the important predisposing factors of palatal fistula in patients who undergo palatoplasty.